Hubungan Tingkat Kebisingan Dengan Volume Kendaraan, Kecepatan, dan Kepadatan lalu Lintas Pada Kondisi Arus Stabil - Lakawa, Irwan; Hujiyanto, Hujiyanto; Syamsuddin, Syamsuddin; Hendriyansa, Muh. (Universitas Sulawesi Tenggara, 2025)
Based on several previous studies, it was found that there were differences in justifications regarding the influence of volume, speed, and traffic density on the level of noise on the highway. The aim of this research was to analyze the influence of volume, speed, and density on the noise level. The research method used a descriptive and parametric statistical approach. The results of the study indicated that the influence of vehicle volume on noise was 46.6% with a direct relationship. The influence of speed on noise was 5.6% with an inverse relationship. The influence of traffic density on noise was 64.8% with a direct relationship. The traffic density variable had the greatest impact on the noise level on the highway. The relationship between vehicle speed and noise was inverse only up to a speed of 70 km/h. If the average vehicle speed exceeded 70 km/h, it was possible for there to be a direct relationship, meaning that as the vehicle speed increased, the noise level also increased.